Pre-eclampsia like Syndrome, a Hypothyroidism Rare Complication: Update on Realities and Controversies - Russu , Manuela Cristina (Research Highlights in Disease and Health Research Vol. 8, 2023)
Pre-eclampsia like syndrome(PLS) or “atypical”/”uncommon” pre-eclampsia(PE) or “very early” PE or PE “imitator” is a rare, severe pregnancy complication, with onset from 14 to 20 weeks, or after 48 hours postpartum, different to “conventional”/”canonical” PE with onset after 20 weeks or in the first 48 hours postpartum. PLS was first described in multipara, elder women, suffering from hypothyroidism, and later in association to chronic hypertension, kidney and autoimmune diseases- inclusive Hashimoto’s thyroiditis, anti-phospholipid syndrome, triploidy, trophoblastic disease, multicystic placenta, primipaternity, COVID-19 or no previous/associated pregnancy disorder. PLS in known/unknown hypothyroidism is characterized by persistent hypertension, under hypotensive drugs, proteinuria aggravated from day–to–day. progressive systemic and cavities edema. The patho- mechanisms, less analyzed in comparison to other PE types, are different from those of “conventional” PE. Overt/subclinical hypothyroidism, isolated hypothyroxinemia induce a very early endothelial inflammatory dysfunction with vasoconstriction/high arterial stiffness in systemic and kidneys’ circulation, and a diastolic disorder, with changes in plasma volume; high TSH are correlated to endothelin high levels. Plasma volume changes are initiating volume-dependent mechanism of reduced plasma renine activity, and increasing proteinuria as nephrotic syndrome, with increased excretion of thyroxine and thyroid-binding globulins, difficult to be compensated, and hypothyroidism aggravation. One may record association of hemolysis, elevated liver enzymes, low platelets (HELLP syndrome). The diagnosis is a challenge to distinguish hypothyroidism driven to PLS from other “atypical” PEtypes, to primary glomerulopathies, according to interplay between hypothyroidism and PE: uterine arteries/ both ophthalmic arteries Doppler studies at 11-14 weeks gestation, soluble fms-like tyrosine kinase–to– placental growth factor serum ratio, and mainly TSH assessment with correct longitudinal interpretation, sometimes kidney’s biopsy make the differences. High doses levothyroxine are mandatory, sometimes liothyronine may save maternal life, not fetuses, mothers having high risks for future cardiovascular, metabolic events, cancers, - associated to adult population cardiometabolic phenotypes.